Vibrational spectroscopic signatures, effect of rehybridization and hyperconjugation on the dimer molecule of N–(4–chlorophenyl)–2–[(4, 6–di–aminopyrimidin–2–yl)sulfanyl]acetamide- quantum computational approach. Issue 7 (9th August 2022) - Jenepha Mary, S. J.; Pradhan, Sayantan; James, C.
Abstract: The antiviral active molecule N–(4–chlorophenyl)–2–[(4, 6–di–aminopyrimidin–2–yl)sulfanyl] acetamide has been characterized to obtain vibrational signatures via Raman and Fourier transform infrared spectroscopy, comparing the results generated by ab initio calculations. The density functional theory model, performed by GAUSSIAN 09 packages, based on the Becke, 3-parameter, Lee–Yang–Parr exchange correlation functions augmented with 6–311++(d, p) basis set. The geometric equilibrium, inter and intra-molecular hydrogen bond, and harmonic vibrational wavenumbers of N–(4–chlorophenyl)–2–[(4, 6–di–aminopyrimidin–2–yl)sulfanyl]acetamide were explored with density functional theory. The stereo-electronic interactions, leading to stability were confirmed using natural bond orbital analysis, which has been further substantiated by vibrational spectral analysis. Hirshfeld surface gives an insight into intermolecular contacts within the Crystal structure. The optimized geometry shows a non-planar structure between the phenyl ring and the pyrimidine ring. Differences in the geometries due to the substitution of the electronegative chlorine atom, intramolecuar and intermolecular contacts due to the amino pyrimidine were analyzed. NBO analysis reveals the formation of two strong stable hydrogen bonded N–H···N intermolecular interactions and weak intramolecular interactions C–H···O and N–H···O. The Hirshfeld surfaces and consequently the 2D-fingerprint confirm the nature of intermolecular interactions and their quantitative contributions toward the crystal packing. The red shift in N–H stretching frequency exposed from IR substantiate the formation of N–H···N intermolecular hydrogen bond. The pharmacokinetic properties were investigated from adsorption, distribution, metabolism, excretion and toxicity results. In-silico docking shows the inhibition activity against virus.